1998
DOI: 10.1086/305813
|View full text |Cite
|
Sign up to set email alerts
|

Optical Continuum and Emission‐Line Variability of Seyfert 1 Galaxies

Abstract: We present the light curves obtained during an eight-year program of optical spectroscopic monitoring of nine Seyfert 1 galaxies: 3C 120, Akn 120, Mrk 79, Mrk 110, Mrk 335, Mrk 509, Mrk 590, Mrk 704, and Mrk 817. All objects show significant variability in both the continuum and emission-line fluxes. We use cross-correlation analysis to derive the sizes of the broad Hβ-emitting regions based on emission-line time delays, or lags. We successfully measure time delays for eight of the nine sources, and find value… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
355
2
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(364 citation statements)
references
References 42 publications
6
355
2
1
Order By: Relevance
“…Using the virial theorem, the mass of a black hole (M BH ) is (Peterson et al 1998;Wandel et al 1999) where ΔV FWHM is the orbital velocity at a radius R BLR of the BLR, and it is estimated by the width of the emission line (specifically, the variable part of the line); f is the factor that depends on the geometry of the BLR. Using a sample disk model for the Arp 102B BLR, one can use the relation derived in Onken et al (2004) …”
Section: Black Hole Mass In Arp 102bmentioning
confidence: 99%
“…Using the virial theorem, the mass of a black hole (M BH ) is (Peterson et al 1998;Wandel et al 1999) where ΔV FWHM is the orbital velocity at a radius R BLR of the BLR, and it is estimated by the width of the emission line (specifically, the variable part of the line); f is the factor that depends on the geometry of the BLR. Using a sample disk model for the Arp 102B BLR, one can use the relation derived in Onken et al (2004) …”
Section: Black Hole Mass In Arp 102bmentioning
confidence: 99%
“…The latter groups used single-epoch spectra to estimate black hole masses and found that the M BH -σ relation of AGNs is shallower than that of quiescent galaxies. One of the main differences between reverberation and single-epoch black hole masses is that the former uses the width of the variable part of the broad emission line measured from root mean square (rms) spectra (Peterson et al 1998). Single-epoch emission-line widths show ∼25% variation when compared with the rms line widths (Vestergaard 2002).…”
Section: The Impact Of Mergers On the M Bh -σ Relationmentioning
confidence: 99%
“…The F W HM can be averaged on all spectra, giving a "mean" BH mass: this is the method preferred by Kaspi et al (2000). In the method proposed by Peterson et al (1998), the F W HM is measured on the rms spectrum, giving a "rms" mass.…”
Section: Relation Between the Optical Luminositymentioning
confidence: 99%